Population level variation in reproductive development and output in the golden kelp Laminaria ochroleuca under marine heat wave scenarios - Fiona-Elaine Strasser; Luis Matos Barreto; Soukaina Kaidi; Brahim Sabour; Ester A. Serrão; Gareth A. Pearson; Neusa Martins (Frontiers in Marine Science, 2022)
Thermal tolerance is often interpreted as a species-wide thermal niche in the absence of studies focusing on the adaptive potential of populations to exhibit differential thermal tolerance. Thus, considering intraspecific thermal plasticity, local adaptation or both between populations along distributional gradients when interpreting and predicting species responses to warming is imperative. Removing the effect of environmental histories by raising kelp gametophyte generations in vitro under common garden conditions allows unbiased comparison between population-specific adaptive variation under different environmental conditions. Following this approach, this study aims to detect (potentially) adaptive differentiation in microscopic life-stages (gametophytes) between populations of a temperate forest forming kelp, Laminaria ochroleuca from locations with distinct thermal conditions. Gametophytes from four geographically distinct populations were subjected to different temperature treatments (17, marine heat waves of 23, 25 and 27°C) and gametophyte survival during thermal stress as well as reproductive success and photosynthetic responses during recovery were investigated. Intraspecific variation in resilience and reproductive output to thermal stress was found in L. ochroleuca ; gametophytes from the most northern population (Brittany, France) were the most thermally sensitive, with mortality onset at 23°C, whereas mortality in the remaining populations was only apparent at 27°C. Gametophytes from northern Spain and Morocco exhibited very low reproductive success during recovery from 23 and 25°C. However, when recovering from the highest thermal treatment (27°C) the reproductive development and sporophyte output was higher than in the gametophytes from France and Italy (Mediterranean). The population-specific responses of gametophyte resilience and reproductive success to temperature stress suggest genetic differentiation in response to variation in local thermal regimes.